The adoption of Google Earth into teaching and learning for tourism geography course / Johanna Adlin Ahmad ... [et al.] - Ahmad, Johanna Adlin (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
The Covid-19 pandemic has changed the spectrum of education where university students need to learn remotely from home. The open and distance learning posed a challenge for the Diploma in Tourism Management students that are learning tourism geography. This is due to the course requiring high visual learning and students need to grasp the knowledge of faraway destinations. This necessitated the lecturers to utilize Google Earth to help facilitate the students to learn tourism geography. Hence, the study aims to explore the adoption of Google Earth in teaching and learning tourism geography courses through the perspectives of the students. The study employed qualitative methods, where a preliminary study conducted involved five participants from semester four of Diploma in Tourism Management students from Universiti Teknologi MARA (UiTM) Pulau Pinang campus. For data analysis, the interview’s content and thematic analysis are presented in the paper. The finding revealed that Google Earth did enhance students’ learning experience through understanding and assisting them to remember the destination. It is also discovered that Google Earth software has the potential to be used in other courses in the program such as tour guiding and planning in tourism. The study contributes to the enhancement of teaching and learning tools whereby by using Google Earth, it can enhance student’s learning and remember tourist attractions better.